Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/ene.12353
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and diagnostic evaluation of chronic polyneuropathies induced by oxaliplatin and docetaxel comparing skin biopsy to quantitative sensory testing and nerve conduction studies

Abstract: Chemotherapy-induced peripheral neuropathy after oxaliplatin or docetaxel treatment is a clinically sensory, axonal neuropathy affecting only small nerve fibres in some patients. NCS are often normal, whereas QST and skin biopsy have a higher diagnostic sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 24 publications
3
62
1
1
Order By: Relevance
“…83 Despite the lack of validation in CIPN, biopsy may have utility when compared to other diagnostic modalities. 84 …”
Section: Detection/diagnosismentioning
confidence: 99%
“…83 Despite the lack of validation in CIPN, biopsy may have utility when compared to other diagnostic modalities. 84 …”
Section: Detection/diagnosismentioning
confidence: 99%
“…Those therapies most likely to produce CIPN include cisplatin [3] oxaliplatin [4,5], vincristine [6,7], paclitaxel [8] and bortezomib [1]. Each of these agents works to kill cancerous cells in differing ways and produces various rates of CIPN.…”
mentioning
confidence: 99%
“…The perception of pinprick pain intensity is related to activity in A- δ fiber nociceptors [35]. Krøigård et al observed in patients with CIPN caused by oxaliplatin and docetaxel that mechanical detection threshold measured with von Frey hairs was more affected as the cold detection threshold [36]. These results indicate that CIPN affects both small and large nerve fibers.…”
Section: Discussionmentioning
confidence: 99%